Structure, conditions and shaping "opponent feeling" in opinion of combat sport athletes - Starosta, W.; Rynkiewicz, T. (Archives of Budo, 2008)
Study aim: the aim of this study was to settle 8 problems connected with "opponent feeling" in combat sports` Material/methods: Studies were conducted on 154 advanced wrestlers in classical style (n =50) and female and male wrestlers in free style (n=11+59=70), 20 kyokushinkai karatekas and 14 wrestling coaches (the age 18-40 years, and the training period was 5-25 years). On all the subjects a survey was conducted using an identical questionnaire, which comprised two parts (the first included information concerning personal data, training period, age, advancement in sport, achievements etc., the second one comprised 21 questions connected with the notion of "opponent feeling", its structure and determining conditions). Results: "Opponent feeling", its contents and structure were difficult, but all the same proved to be feasible for initial defining. This feeling acquires a particular significance in technical mastering at champion level. This fact was admitted by the majority of surveyed athletes. Similarly, as the relation that occurs between this feeling and external conditions. Optimum conditions are advantageous for the manifestation of a higher level of "opponent feeling" and of the technique. It also depends on the psychical state of the athlete. Excessive emotions may affect it in an adverse way, while optimum ones - in a stimulating way. Conclusions: Opinions expressed by the surveyed athletes were formulated in a synthetic way with respect to 12 issues. A lot of them have not been analysed here for lack of available space, even though they present a highly interesting material. Of exceptional value are statements of highly experienced athletes, particularly classical style wrestlers, many of whom belonged to the world elite